AN ANALYSIS OF TRANSLATION STRATEGIES USED IN TRANSLATING FIGURES OF SPEECH IN THE COMPANION PIECE "HOTEL VALHALLA: GUIDE TO THE NORSE WORLDS" - Ricky Ilham Kurniawan (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
This study aims to analyze the translation strategies and translation acceptability of the figurative language that are frequently used in the “Hotel Valhalla” companion book. Due to cultural differences between English and Indonesian languages, literal rendition of these figurative language may not be available and the translator may need to implement strategies to achieve equivalent expressions. The researcher employed a qualitative research approach involving data collection. Based on the result of the study, the researcher identified ninety figures of speech from the book with the following translation strategies: Translation by implementing less-expressive words in a similar figurative language with similar meaning, translation by cultural substitution in a similar figurative language with similar meaning, translation by a paraphrase with related words in a similar figurative language with similar meaning, translation by loaning words in a similar figurative language with similar meaning, translation by implementing similar figurative language with similar meaning, translation by cultural substitution in a different figurative language with similar meaning, translation by a paraphrase with unrelated words in a different figurative language with similar meaning, translation by omission, translation by a paraphrase with unrelated words, and translation by a paraphrase with related words. For the translation acceptability, seventy translations were considered ideally acceptable, sixteen translations were considered less acceptable, and four translations were considered unacceptable. This study indicated that the translator implemented ten translation strategies to translate the figures of speech from the companion piece with most of the translations considered ideally acceptable.